Effect of ceramic thickness, grinding, and aging on the mechanical behavior of a polycrystalline zirconia - Prado, Rodrigo Diniz; Pereira, Gabriel Kalil Rocha; Bottino, Marco Antonio; Melo, Renata Marques de; Valandro, Luiz Felipe (FapUNIFESP (SciELO), 2017)
Monolithic restorations of Y-TZP have been recommended as a restorative alternative on prosthetic dentistry as it allows a substantial reduction of ceramic thickness, which means a greater preservation of tooth structure. However, the influence of grinding and aging when using a thinner layer of the material is unclear. This investigation aimed to evaluate and compare the effects of ceramic thickness (0.5 mm and 1.0 mm), grinding and aging (low-temperature degradation) on the mechanical behavior and surface characteristics of a full-contour Y-TZP ceramic. Y-TZP disc-shaped specimens (15 mm diameter) were manufactured with both thicknesses and randomly assigned into 4 groups considering the factors 'grinding with diamond bur' and 'aging in autoclave'. Surface topography (roughness, 3D profilometry and SEM), phase transformation, flexural strength and structural reliability (Weibull) analyses were executed. Grinding affected the surface topography, while aging did not promote any effect. An increase in m-phase content was observed after grinding and aging, although different susceptibilities were observed. Regardless of zirconia's thickness, no deleterious effect of grinding or aging on the mechanical properties was observed. Thus, in our testing assembly, reducing the thickness of the Y-TZP ceramic did not alter its response to grinding and low temperature degradation and did not impair its mechanical performance.